Evaluating the Use of Sacran, a Polysaccharide Isolated from Aphanothece sacrum, as a Possible Microbicide for Preventing HIV-1 Infection - Matsuda, Kouki; Kariya, Ryusho; Maeda, Kenji; Okada, Seiji (Viruses, 2024)
Since combination antiretroviral therapy (cART) was introduced to treat human immunodeficiency virus type-1 (HIV-1)/acquired immunodeficiency syndrome (AIDS), the AIDS mortality rate has markedly decreased, and convalescence in individuals with HIV has improved drastically. However, sexual transmission has made HIV-1 a global epidemic. Sacran is a megamolecular polysaccharide extracted from cyanobacterium Aphanothece sacrum that exhibits numerous desirable characteristics for transdermic applications, such as safety as a biomaterial, a high moisture retention effect, the ability to form a film and hydrogel, and an anti-inflammatory effect. In this study, we evaluated the anti-HIV-1 effects in sacran as a barrier to HIV-1 transmission. Sacran inhibited HIV-1 infection and envelope-dependent cell-to-cell fusion. Moreover, we used a Transwell assay to confirm that sacran inhibited viral diffusion and captured viruses. The synergistic effects of sacran and other anti-HIV infection drugs were also evaluated. HIV-1 infections can be reduced through the synergistic effects of sacran and anti-HIV-1 drugs. Our study suggests using sacran gel to provide protection against HIV-1 transmission.